التَوسع الإئتماني في مجال القروض العقارية بين ضرورة الإنفتاح الإقتصادي ومخاطر التحصيل - بن موسى ., صفاء; بن شيخ, هشام (University of Eloued جامعة الوادي, 2021)
يهدف هذا البحث إلى بيان ظاهرة التوسع الإئتماني في مجال منح القروض العقارية كنتيجة حتمية في ظل الإنفتاح الإقتصادي على المستويين الوطني والدولي على حد السواء, وكذا مخاطر الإئتمان التي تتعرض لها البنوك والمؤسسات المالية المانحة للقرض العقاري في ظل التسهيلات المتاحة للمقترضين, ممَا يجعلها عرضة لخسائر مالية عندما يفشل بعض المقترضين في سداد قروضهم على النحو المتفق عليه. Abstract: This study aims at shedding light on the expansionist phenomenon in the domain of mortgages as a fatal outcome in the light of the economic openness on the national and international levels. Furthermore, it shows the credit risks to which the banks and the financial institutions that give mortgages are subject to in the light of the facilities provided for the borrowers. This makes them subject to financial losses when some borrowers fail to pay back according to the agreement.
redit Expansion in Mortgages Between the need for Economic Openness and the risks of Debt Collection
مقال
Keywords: الإئتمان ؛ القرض العقاري ؛ مخاطر التحصيل ؛ التسهيلات الإئتمانية ؛ الإنفتاح الإقتصادي; Credit- mortgage- debts collection risks- credit facilities- economic openness